Assessing water quality of Murum Reservoir halfway through impoundment - Angie Sapis,; Lee, Nyanti; Ling, Teck Yee; Sim, Siong Fong; Jongkar Grinang, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper reports the water quality of Murum Hydroelectric Reservoir, eight months after impoundment of the dam. A total of nine stations were selected in the reservoir. Temperature, pH, dissolved oxygen (DO), biochemical oxygen demand (BOD5), chlorophyll-a and total suspended solids (TSS) were studied. The results showed that the water was warmer at 0.5 m depth. As the depth increased, temperature in the reservoir decreased in the range of 4.40°C to 7.35°C from 0.5 to 20 m depth. The concentration of DO dropped to zero at 4 - 6 m depth leading to anoxic level. pH at 0.5 m depth ranged from 6.40 to 7.20 and they were significantly higher (p<0.05) than those at 10 and 20 m. Chlorophyll-a at 0.5 m were in the range of 4.61 to 20.50 mg/L, relatively higher compared to 10 m and 20 m depths. The results obtained indicates that impoundment of Murum River generally caused water quality deterioration. In addition, this could be due to anthropogenic activities such as plantation and logging activities that are still going on within the catchment during the impoundment. Therefore, further continuous monitoring and investigation is required to determine the long-term water quality condition and identify factors that influence water quality in Murum Reservoir.